PENINGKATAN PEMAHAMAN SAINS BIOLOGI MELALUI PERMAINAN KARAMBOL - SUBHAN, SUBHAN (JPUD - Jurnal Pendidikan Usia Dini, 2017)
The aim of this study is to describe the process and results of learning through play carom that can improve scientific understanding of biological children in RA B1 Salsabila Jakarta Year 2015/2016. The subjects of this study were 22 children. This research method is based on the Research Action Class Action Research model Kemmis and Mc. Taggart which includes four stages: planning, action, observation, and reflection. This study consisted of two cycles, each cycle consisting of 8 times pertemuan.Teknik data analysis used in this research is the analysis of qualitative and quantitative data. Analysis of qualitative data by analyzing data from interviews during the study to the steps of data reduction, data display and data verification. Quantitative data analysis with descriptive statistics to compare the results obtained from pre-intervention, the first cycle and the second cycle. The results of this study showed an increased understanding of sains biologi children through play carom, evidenced by an average understanding of sains biologi score of 41.59 pre-intervention, then increased in the first cycle of the second cycle of 63.82 and 80.73.